2021
DOI: 10.1093/bib/bbab213
|View full text |Cite
|
Sign up to set email alerts
|

Detecting SARS-CoV-2 and its variant strains with a full genome tiling array

Abstract: Coronavirus disease 2019 pandemic is the most damaging pandemic in recent human history. Rapid detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and variant strains is paramount for recovery from this pandemic. Conventional SARS-CoV-2 tests interrogate only limited regions of the whole SARS-CoV-2 genome, which are subjected to low specificity and miss the opportunity of detecting variant strains. In this work, we developed the first SARS-CoV-2 tiling array that captures the entire SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…For the tiling array, the processing duration from RNA virus to sequencing data is controlled within one day. Whole genome FASTA and FASTQ files are output using customized software based on a bioinformatics protocol of two base calling methods [ 12 ]. According to the Sanger sequencing results in this study and the previous reports, this assay accompany the base calling algorithms has ability to discover mutations with a genome-wide accuracy of at least 99.5% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the tiling array, the processing duration from RNA virus to sequencing data is controlled within one day. Whole genome FASTA and FASTQ files are output using customized software based on a bioinformatics protocol of two base calling methods [ 12 ]. According to the Sanger sequencing results in this study and the previous reports, this assay accompany the base calling algorithms has ability to discover mutations with a genome-wide accuracy of at least 99.5% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome FASTA and FASTQ files are output using customized software based on a bioinformatics protocol of two base calling methods [ 12 ]. According to the Sanger sequencing results in this study and the previous reports, this assay accompany the base calling algorithms has ability to discover mutations with a genome-wide accuracy of at least 99.5% [ 12 ]. More importantly, this method is highly cost-efficient with $30 per sample and high throughput with 96 parallel testing abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosensors based on SPR, CRISPR/Cas, LAMP and aptamers have been also proposed for the detection of other SARS-CoV-2 point mutations ( Xi et al, 2021 ). Other approaches developed recently for detecting SARS-CoV-2 point mutations include a toolset for qPCR-based SNP detection ( Noerz et al, 2021 ) and full genome tiling array that can analyze the whole SARS-CoV-2 genome at single nucleotide resolution ( Jiang et al, 2021 ). Dual synthetic mismatches CRISPR/Cas12a (dsmCRISPR) method for the detection of D614G mutation with high specificity and sensitivity has been presented recently ( Huang et al, 2021 ).…”
Section: Detection Of Point Mutations In Viruses By Biosensorsmentioning
confidence: 99%
“…There are over 255.1 million confirmed cases worldwide and over 5.12 million deaths, involving more than 200 countries and regions [1]. Variant strains have been found in many countries and regions [2,3], such as India, the United States, France, and Germany, and more studies have shown that variant strains are associated with higher mortality [4]. Many countries have begun encouraging vaccinations, promoting education, and strengthening food cold-chain testing [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%